Relationship between dietary inflammatory index and metabolic dysfunction associated steatotic liver disease in children - Fateme Amiri; Jalal Moludi; Touraj Ahmadi Jouybari; Mahmoud Ghasemi; Maryam Sharifi; Behzad Mahaki; Davood Soleimani (Scientific Reports)
Abstract Emerging research suggests a connection between dietary habits and metabolic dysfunction associated steatotic liver disease (MASLD). We aimed to assess the relationship between the Dietary Inflammatory Index (DII) and the severity of MASLD. This cross-sectional study involved 125 participants aged 7–18 with MASLD. Dietary intakes were assessed using a validated 147-item food frequency questionnaire. The DII was applied to measure diet-induced inflammation, categorizing diets into anti-inflammatory (DII < -1) and inflammatory diets (DII > + 1). To evaluate hepatic steatosis and fibrosis, transabdominal ultrasonography and the fibrosis-4 (FIB-4) index were utilized. After adjusting for potential confounding factors, individuals on inflammatory diets exhibited a significantly higher odds ratio (OR) for experiencing more severe steatosis (OR: 4.11; 95% CI: 1.08–15.71) compared to those on anti-inflammatory diets. Furthermore, each unit increase in DII scores was linked to a 2.6-fold increase in the odds of more severe steatosis (OR: 2.61; 95% CI: 1.28–5.32) and a 0.006 increase in FIB-4 scores (β: 0.006; 95% CI: 0.003–0.011). In conclusion, modifying dietary intakes to lower DII scores may be a beneficial approach to improving clinical outcomes in pediatric MASLD, as anti-inflammatory diets are associated with reduced severity of hepatic steatosis and fibrosis.